The Relationship Between Food Safety Knowledge and Attitudes, Personal Hygiene Behavior in Hawker Traders in Pasir Gombong Village - Burhanuddinnisa, Amanda Shifa; Kinayungan, Utami Putri; Sanjaya, Dandi; Nurpratama, Widya Lestari (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Food safety is an effort to prevent food contamination that threatens health. Foodborne disease remains a global issue, including in Indonesia, as seen in poisoning cases in Bekasi and Cikarang. Street food is still at risk of being unhygienic, as many vendors neglect hygiene due to limited information, capital, and guidance. Knowledge and attitude are important factors in maintaining personal hygiene. Objective: This study aims to analyze the relationship between food safety knowledge and attitudes with the personal hygiene of street food vendors in Pasir Gombong Village. Methods: This study employed an analytical design with a cross-sectional approach. The sample consisted of 50 street food vendors in Pasir Gombong Village. Data were collected using a questionnaire, and the Chi-Square test was applied to examine variable relationships. Results and Discussion: The statistical test showed a p-value of 1.000 for the relationship between knowledge and personal hygiene, and 0.170 for the relationship between attitude and personal hygiene (p > 0.05). These results indicate no significant relationship. Conclusion: Most respondents were male, middle-aged, well-educated, experienced in trading, and had middle to high income, but had never attended food safety training. Although respondents generally had good knowledge, attitudes, and hygiene practices, statistical analysis showed no significant association between knowledge or attitudes and personal hygiene